New Modes of Governance in the Global System
XII, 262 p.
Keywords: Globalization processes are propelling a transformation of governance. As political problems become more transnational, public as well as private actors increasingly perform governance activities beyond the level of individual states. This book examines the wide variety of forms that governance can take in the global system and their consequences. An overarching analytical framework is applied to global institutions and initiatives in areas such as trade liberalization, financial market regulation, privacy protection, cybercrime, and food safety.